KUALIFIKASI JURNALIS PEMULA PADA RADIO ANAK MUDA DI JAWA BARAT - Achmad Abdul Basith (Communicology: Jurnal Ilmu Komunikasi, 2018)
ABSTRACT Radio broadcast continues to play a role in the distribution of information through its broadcast programs. As a mass media radio broadcasts not only have a function as an entertainment medium with songs that are played, but also have a function to educate and convey information. So the existence of journalists in each radio broadcast becomes an obligation. But in practice, this journalist function is not only attached to those who seek information in the field, but also those who work in the studio as broadcasters and program producers. As a mass media with a variety of program formats, radio broadcasts have diverse needs for beginner journalists. There are those who require the beginning journalist to only have sound quality and good announcing techniques, but not a few who require the beginning journalist to have good general knowledge, perseverance, and sometimes the appearance is also one of the things considered. The reason is that journalists also represent the radio, especially for those who work outside the studio. In this study, we used descriptive qualitative research. The study was conducted to broadcast radio managers with the segmentation of young people in West Java, represented by Ardan Bandung (representing greater Bandung), Radio eMDiKey (representing Priangan Timur), Radio Pilar (representing Cirebon dsk). We consider these three regions capable of representing West Java. The results of this study indicate that the qualifications of beginner journalists on radio are more emphasized in their attitude and militancy in the field. Regarding the relevance of formal education that has been taken by prospective journalists is not the main problem. The average implements re-adjustment (training) before actually being adopted as a crew on broadcast radio. The physical appearance factor is one that is considered even though it is not the main one. Keywords: radio, journalists, young people, West Java ABSTRAK Radio siaran terus memainkan peran dalam distribusi informasi melalui program siarannya. Sebagai media massa radio siaran tidak hanya memiliki fungsi sebagai media hiburan dengan lagu-lagu yang diputarkan, tetapi juga memiliki fungsi untuk mendidik dan menyampaikan informasi. Maka keberadaan jurnalis di setiap radio siaran menjadi sebuah kewajiban. Namun dalam praktiknya, fungsi jurnalis ini tidak hanya menempel pada mereka yang mencari informasi di lapangan, tetapi juga mereka yang bekerja di studio sebagai penyiar maupun sebagai produser program. Sebagai media massa dengan bermacam format program, radio siaran memiliki kebutuhan akan jurnalis pemula yang beragam. Ada yang mensyaratkan jurnalis pemulanya sekadar memiliki kualitas suara dan teknik announcing yang baik, tapi tak sedikit yang mewajibkan jurnalis pemulanya memiliki pengetahuan umum yang baik, gigih, serta kadang penampilan juga menjadi salah satu hal yang dipertimbangkan. Alasannya, jurnalis juga menjadi representasi dari radio tersebut, khususnya bagi yang bertugas di luar studio. Dalam penelitian ini, kami menggunakan penelitian kualitatif deskriptif. Penelitian dilakukan kepada pengelola radio siaran dengan segmentasi anak muda di Jawa Barat yang diwakili Ardan Bandung (mewakili greater Bandung), Radio eMDiKey (mewakili Priangan Timur), Radio Pilar (mewakili Cirebon dsk). Tiga daerah ini kami anggap mampu merepresentasikan Jawa Barat. Hasil dari penelitian ini menunjukkan bahwa kualifikasi jurnalis pemula pada radio lebih ditekankan pada sikap dan militansi mereka di lapangan. Perihal relevansi pendidikan formal yang pernah ditempuh oleh calon jurnalis itu bukan masalah utama. Rata-rata menerapkan penyesuaian kembali (training) sebelum benar-benar di angkat sebagai kru di radio siaran. Faktor penampilan secara fisik menjadi salah satu yang dipertimbangkan meski bukan yang utama. Kata Kunci: radio, jurnalis, anak muda, Jawa Barat